Analgesic effect of breastfeeding for minor procedures in neonates: changing routines - Elisa Sánchez Torres (Fundación para el Desarrollo de la Enfermería, 2013)
With newborns often do you puncture to draw blood for diagnostic tests (hypoglycemia, hyperbilirubinemia, etc.) as well as to conduct metabolic tests, causing pain during the procedure. Reduce and even eliminate pain in neonates is essential for them and their parents.Numerous studies have measured and analyzed the response to pain in neonates and as different techniques and use of drugs to reduce it.The aim of this study is to assess whether the pain is reduced in infants through breastfeeding simultaneously and skin contact, in order to change routines in the Obstetrics Unit of Hospital Universitario de Fuenlabrada. To do this, we designed a pilot study, establishing two groups of babies who are going to puncture and subsequent assessment of response to pain. The intervention group will be composed of infants who underwent simultaneous breast-feeding puncture skin and skin with the mother and the control group, infants who underwent the puncture in the nursing, the mother may accompany your child to the same (standard procedure).